The conditional contribution mechanism for repeated public goods: the general case - Oechssler, Joerg; Reischmann, Andreas; Sofianos, Andis (Journal of economic theory, 2022)
We present a new and simple mechanism for repeated public good environments. In the Conditional Contribution Mechanism (CCM), agents send two messages of the form, “I am willing to contribute x units to the public good if in total y units are contributed.” This mechanism offers agents risk-free strategies, which we call unexploitable. Our main theorem states that all outcomes of the CCM will eventually be Pareto efficient if agents choose unexploitable better responses. We conduct a laboratory experiment to investigate whether observed behavior is consistent with this prediction. In the complete information case we find that indeed almost 80% of outcomes are Pareto optimal. Furthermore, in comparison to the Voluntary Contribution Mechanism, the CCM leads to significantly higher contribution rates. Even under incomplete information, contributions are fairly high and do not deteriorate over time, although surprisingly the VCM does equally well in this case. Theoretically, allowing agents to send two messages helps them ensure the status-quo and at the same time offer higher contribution levels. In a further treatment, where we allow agents to send only one message, we find that total contributions are consistently lower than the CCM in early periods but are similar in later periods.
Available online 24 May 2022
Gesehen am 08.06.2022